Organizing the Election Campaign and Its Methods from the Perspective of Iraqi law : An Analytical Overview - Hawar Muhammed yousif (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
An election campaign is a media advertisement carried out by political parties and candidates, to run in the elections, relying on material and moral capabilities, to reach effective rationalization that leads to the arrival of the targeted and planned message to the future. The electoral process is not a legitimate means but it is a basic means to exercise political work. The fair election campaign has become one of the means of transparency. While talking about Electoral integrity, the election campaign is an aid to choose what is a lineage to represent him/her in power. The method used in our study is the descriptive, analytical, and critical approach. The study aims to evaluate the election campaign which is one of the stages in the election process and political work. It is found from this study that the available means for the entities and candidates participating in the electoral process are equal and identical to the international provisions and norms followed in this field in accordance with the Iraqi law too. It is also found that we also find in the shadow of the Independent High Electoral Commission in Iraq and the judicial bodies Concerning this issue, the electoral campaign is organized and guarantees equality for all.